Characteristics of inflammatory reactions in the tumor microenvironment of head and neck squamous cell carcinoma - V. A. Bychkov; L. N. Bondar; L. A. Tashireva; O. V. Cheremisina; E. L. Choynzonov; V. M. Perelmuter (Сибирский онкологический журнал, 2019)
Objective: to analyze the association between inflammatory cells with morphological heterogeneity and lymphogenous metastasis of head and neck squamous cell carcinoma.Material and Methods. Five types of tumor structures, the level of inflammatory infiltration and the counts of CD4+ and CD8+ t-lymphocytes, B-lymphocytes and macrophages in the stromal infiltrate and Langerhans cells in tumor structures were assessed in 44 patients.Results. The presence of Langerhans cells in type 1 structures was correlated with the presence of CD3+ and CD4+ t-cells in the inflammatory infiltrate. There was a decrease in the inflammatory reaction and the number of CD3+ T cells in patients with metastatic lymph nodes compared with patients with intact lymph nodes. In patients with lymph node metastasis, the proportion of CD4+ and / or CD8+ and / or CD20+ lymphocytes in the infiltrate was higher in cases with well-differentiated tumor than in cases with poorly-differentiated tumor.Conclusion. The results obtained showed the decrease in the level of inflammatory response, including t-cell response, as well as the relationship between the presence of Langerhans cells and stromal inflammatory response in patients with lymph node metastasis.